Evaluation of Web GIS Applications and their Development Tools Using AHP - Miroslav Pásler (Acta Informatica Pragensia, 2015)
The Analytic hierarchy process (AHP) is a widely used approach in the field of decision making, evaluation and group decision making processes. It is popular especially for its specifics related to consistency of an evaluator's decisions and an approach to decomposition of a certain problem. AHP and its forms are also exploited in the area of geographic information systems (GIS) while solving variety of multiple problems. In this article the role of AHP is a method of determining a set of criteria and weights of the criteria of evaluating Web GIS applications which are presenting points of interest and of evaluating the development tools. Within the research weights of criteria were defined by interviewing evaluators divided into categories according to their relationships to creation and usage of Web GIS applications. The evaluation process focuses on a particular Web GIS map presentation. The article compares results of this research with results of previous works which were searching for the best development tool of similar Web GIS applications. This article also includes an assessment of evaluators' decision making consistency according to their categories.